The Role of Modern Administrative Accounting Methods in the Quality of Administrative Decisions (A Field Study on a Sample of Industrial Companies in the Syrian Coast) - قاسم سامر; ريم محمد نصور (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The aim of the research is to study the role of modern administrative accounting methods (activity-based costs, total quality management, balanced scorecard) in the quality of administrative decisions. The researchers relied on the analytical descriptive approach as a general approach to research, where a questionnaire was designed and distributed to an easy sample of workers at the upper and middle administrative levels in a number of industrial organizations in the Syrian coast (170, retrieved 163 valid questionnaire for statistical analysis), and the researchers used the statistical program (SPSS) in conducting statistical characterization and testing research hypothesis. The research found that modern administrative accounting methods are used to a high degree, and administrative decisions are of a high degree of quality in industrial organizations in the Syrian coast, and found a positive moral effect for the modern administrative accounting methods in the quality of administrative decisions.